Frontal theta oscillations and cognitive flexibility: Age-related modulations in EEG activity - Margarita Darna; Christopher Stolz; Hannah-Sophia Jauch; Hendrik Strumpf; Jens-Max Hopf; Constanze I. Seidenbecher; Björn H. Schott; Anni Richter (Aging Brain)
Cognitive flexibility, the ability to adapt one’s behaviour in changing environments, declines during aging. Electroencephalography (EEG) studies have implicated midfrontal theta oscillations in attentional set-shifting, a measure of cognitive flexibility. Little is known about the electrocortical underpinnings of set-shifting in aging. Here, we investigated aging effects on set-shifting performance by analysing theta power in 20 young (mean age: 22.5 ± 2.9 years) and 19 older (mean age: 69.4 ± 6.1 years) adults. Increasing shift difficulty (i.e., intra- vs. extra-dimensional shifts) elicited worse performance in both age groups, with older adults showing overall longer reaction times (RTs) and increased RT variability. Young adults exhibited amplified midfrontal theta power increases with higher shift difficulty whereas older adults showed overall lower theta power and no task-related midfrontal theta power modulation, indicating potentially distinct underlying neural mechanisms.